Bibliometric Analysis of Special Needs Education Keyword Using VOSviewer Indexed by Google Scholar - Dwi Novia Al Husaeni; Asep Bayu Dani Nandiyanto; Rina Maryanti (Indonesian Journal of Community and Special Needs Education, 2023)
Special needs education is a field of study that focuses on providing educational services to children with special needs who have learning and developmental challenges. The goal of this research is to combine mapping analysis with the VOSviewer app. The Publish or Perish application is used to find publications that are relevant to the keywords that have been entered. The term "Special Needs Education" was utilized in this study as a keyword. According to the search results, 400 relevant articles were published between 2017 and 2021. The number of publications published on "Special Needs Education" has declined every year, according to the research findings. This study should aid researchers in conducting and determining the research theme.